A Fast and Efficient Thinning Algorithm for Binary Images - Tarik Abu-Ain; Siti Norul Huda Sheikh Abdullah; Bilal Bataineh; Khairuddin Omar (Journal of ICT Research and Applications, 2013)
Skeletonization "also known as thinning" is an important step in the pre-processing phase in many of pattern recognition techniques. The output of Skeletonization process is the skeleton of the pattern in the images. Skeletonization is a crucial process for many applications such as OCR and writer identification. However, the improvements in this area are only a recent phenomenon and still require more researches. In this paper, a new skeletonization algorithm is proposed. This algorithm combines between parallel and sequential, which is categorized under an iterative approach. The suggested method is conducted by experiments of benchmark dataset for evaluation. The outcome is to obtain much better results compared to other thinning methods that are discussed in comparison part.